STARCH FRACTIONS OF COOKED POTATOES AT LOW TEMPERATURE - Raigond, Pinky; Ezekiel, R; Kaundal, Bhawna (Potato Journal, 2014)
Consumption of boiled potatoes stored for one or two days in a refrigerator is a common practice. This study was carried out to measure the potential of three Indian potato cultivars for resistant starch (RS) formation during domestic cooking and storage. Hence, the effect of cooking (boiled, microwave cooked, pressure cooked) followed by low temperature storage (4 and 12Â°C) for different durations (12 and 48 hour) on content of starch fractions was studied. The study showed that decrease in starch content in cooked potato tubers was accompanied by an increase in reducing sugars and sucrose contents. Cooling of cooked tubers at 4Â°C for 48 hour resulted in 7% reduction in starch content, 63% increase in RS content and 7% reduction in rapidly digestible starch content, but 35% increase in reducing sugars and 40% increase in sucrose contents. Low temperature storage can be beneficial in increasing the RS content considerably but the increase in reducing sugars and sucrose contents can offset this benefit. The increase in RS content after cooling was higher in boiled tubers as compared to microwave and pressure cooked tubers. Cultivar Kufri Bahar has higher tendency to form RS in boiled and cooled tubers compared to Kufri Jyoti and Kufri Sindhuri.